1969
DOI: 10.1029/jb074i002p00711
|View full text |Cite
|
Sign up to set email alerts
|

Solar eclipse: Temperature, wind, and ozone in the stratosphere

Abstract: The occurrence of a total eclipse at Tartagal, Argentina, on November 12, 1966, prompted a rocket sounding experiment to determine temperature, wind, and ozone perturbations in the stratosphere caused by the eclipse. Soundings were made in the 65-to 30-km region of the atmosphere before, during, and after the total eclipse. Twelve rockets were successfully fired; nine of the rocket instruments were designed to measure temperature and three were designed to determine ozone concentration in the atmosphere. Wind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…This result is in agreement with Eckermann et al (2007) who obtained similar values for the 2002 total solar eclipse with a prototype high-altitude global numerical weather prediction model. However, Eckermann et al (2007) pointed out that several rocket soundings reported temperature decreases of 5-12 K at 50-60-km altitude during solar eclipses (Ballard et al 1969;Quiroz and Henry 1973;Randhawa 1974;Schmidlin and Olsen 1984). It is thus possible that the amplitude of the stratospheric thermal forcing term was not properly estimated in our model.…”
Section: ) Stratospheric Responsementioning
confidence: 67%
“…This result is in agreement with Eckermann et al (2007) who obtained similar values for the 2002 total solar eclipse with a prototype high-altitude global numerical weather prediction model. However, Eckermann et al (2007) pointed out that several rocket soundings reported temperature decreases of 5-12 K at 50-60-km altitude during solar eclipses (Ballard et al 1969;Quiroz and Henry 1973;Randhawa 1974;Schmidlin and Olsen 1984). It is thus possible that the amplitude of the stratospheric thermal forcing term was not properly estimated in our model.…”
Section: ) Stratospheric Responsementioning
confidence: 67%
“…Some rocket soundings of the middle atmosphere have reported temperature decreases in the 5–12 K range at 50–60 km altitude during eclipse passages [ Ballard et al , 1969; Quiroz and Henry , 1973; Randhawa , 1974; Schmidlin and Olsen , 1984]. Quiroz and Henry [1973] and Schmidlin and Olsen [1984] also reported substantial increases in meridional wind speeds, peaking at 20–40 m s −1 at ∼60 km, which Quiroz and Henry [1973] interpreted as a balanced circulation response to eclipse‐induced changes in the lateral temperature gradients.…”
Section: Discussionmentioning
confidence: 99%
“…The eclipse swept over South Korean peninsula with starting phase at 00:30 UT (09:30 KST) and ending phase at 03:13 UT (12:13 KST) with maximum at 01:47 UT (10:47 KST), respectively, having maximum solar obscuration of about ~84%. The total solar eclipse effects include the variations not only in the ion/electron densities but also in the other background parameters such as magnetic field, temperature and neutral compositions [1]. The effects of solar eclipse on different regions of the atmosphere have been studied extensively by different ground based instruments (coherent and incoherent scatter radars) [3] and satellite based measurements (Global positioning system (GPS), Constellation Observing System for Meteorology Ionosphere and Climate (COSMIC) etc.)…”
Section: Introductionmentioning
confidence: 99%